Examining the Moderate Understanding of Islam among Higher Education Students of the State Institute of Islamic Studies Surakarta - Toto Suharto (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
The study of radicalism among students of the State Institute of Islamic Studies (IAIN), Surakarta, showed a significant increase within the recent decade. Hence, this article attempts to analyze the level of moderate understanding of these students with a survey that involved 100 persons. The past educational background of each student was deeply explored to figure out the basics of their religious understanding. Meanwhile, qualitative and quantitative designs were employed to measure their understanding of moderate Islam. The results of the study showed that the students of IAIN Surakarta had a moderate understanding of Islamic teachings, according to an outcome of 87%. The high value was because the majority of the respondents had graduated from madrasah and pesantren, which had strongly emphasized cultivating moderate religious doctrines. This outcome was different from that of general high school graduate students, where they learned the doctrines from Rohani Islam or Rohis. Also, it was discovered that the Rohis commonly hold radical and intolerant religious doctrines. This is understandable as this community tends to understand Islamic doctrines textually, scripturally, and differently from the teachings promulgated by pesantren and madrasa.